1995
DOI: 10.1021/la00002a012
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Diffraction Study of the Ordered Lyotropic Phases Formed by Sugar-Based Surfactants

Abstract: In this work we investigate lyotropic phases in different sugar-based surfactantlwater systems. Studies are carried out with the (N-alky1amino)-1-deoxylactitols (CS, C10, CIZ) and P-dodecyl maltoside. Liquid crystal phases are detected and lattice parameters determined by X-ray diffraction. The phases observed are the normal phases found in binary ionic or nonionic surfactantlwater systems. Schematic diagrams show the sequences of the lyotropic phases formed by these disaccharide surfactants. The difference in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 5 publications
2
62
0
Order By: Relevance
“…The gregates in a hexagonal array. The L phase is in equilibrium phase appears to be composed of flexible bimolecular sheets with the hexagonal liquid crystalline phase at high surfactant of infinite area but arranged in parallel to each other (18). concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The gregates in a hexagonal array. The L phase is in equilibrium phase appears to be composed of flexible bimolecular sheets with the hexagonal liquid crystalline phase at high surfactant of infinite area but arranged in parallel to each other (18). concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…No efforts have been made to link the thermotropic and lyotropic properties, although these substances form micelles and lyotropic liquid crystals [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…There has recently been much research dealing with the effects of nonaqueous polar solvents on the formation of cationic micelles (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Micel!e or liquid crystal formation has been reported to occur in such solvents as hydrazine (3,4), glycerol (5,6), ethylene glycol (7,8), and formamide (9)(10)(11)(12)(13)(14)(15)(16)(17)(18), where all of the aforementioned solvents have high cohesive energy, dielectric constant, and a high degree of hydrogen bonding. Evans and co-workers (19) have indicated that the ability of a solvent to form hydrogen bonds is a necessary condition of micelle formation.…”
Section: Introductionmentioning
confidence: 99%